Functionalization of an experimental Ti-Nb-Zr-Ta alloy with a biomimetic coating produced by plasma electrolytic oxidation - Cordeiro, Jairo M.; Nagay, Bruna E.; Ribeiro, Ana Lúcia R.; da Cruz, Nilson C. [UNESP]; Rangel, Elidiane C. [UNESP]; Fais, Laiza M.G. [UNESP]; Vaz, Luís G. [UNESP]; Barão, Valentim A.R. (Elsevier, 2019)
This study developed an experimental quaternary titanium (Ti) alloy and evaluated its surface properties and electrochemical stability. The viability for a biofunctional surface treatment was also tested. Ti-35Nb-7Zr-5Ta (wt%) alloy was developed from pure metals. Commercially pure titanium (cpTi) and Ti-6Al-4V were used as controls. All groups had two surface conditions: untreated (machined surface) and modified by plasma electrolytic oxidation (PEO) (treated surface). The experimental alloy was successfully synthesized and exhibited β microstructure. PEO treatment created a porous surface with increased roughness, surface free energy, hardness and electrochemical stability (p < 0.05). For the machined surfaces, the Ti-Nb-Zr-Ta alloy presented the lowest hardness and elastic modulus (p < 0.05) and displayed greater polarization resistance relative to cpTi. Only PEO-treated cpTi and Ti-Al-V alloys exhibited anatase and rutile as crystalline structures. The β experimental Ti-Nb-Zr-Ta alloy seems to be a good alternative for the manufacture of dental implants, since it presents elastic modulus closer to that of bone, feasibility for surface treatment, electrochemical stability and absence of toxic elements.
Keywords: Bioactive coating; Corrosion; Dental implant; Metals and alloys; Surface property; Titanium